A Scaffold-Based Approach for Developing an English Coursebook for Young Learners - Kristanto, Barlian; Setia Sandi A., Arif; Putri, Diannike; Ferianda, Sandy; Dung, Le Hoang (Universitas Sarjanawiyata Tamansiswa, 2024)
This study aimed to develop and evaluate the effectiveness of a scaffolding-based English coursebook for 3rd-grade elementary students in Indonesia. The research was conducted in response to the challenges faced by teachers and young learners in , English language education, such as lack of contextualized materials and student engagement. A mixed-methods design was employed, involving a needs assessment, coursebook design, and a quasi-experimental study with 120 students from two schools in Purwokerto, Central Java. The experimental group used the scaffolding-based coursebook, while the control group used existing materials. The results revealed significant improvements in English proficiency scores for both groups, with the experimental group outperforming the control group. Qualitative data from classroom observations and interviews indicated increased student engagement, motivation, and positive perceptions of the scaffolding approach in the experimental group. The findings suggest that the scaffolding-based coursebook effectively enhanced young learners' English language proficiency and engagement compared to existing materials. The study highlights the potential of scaffolding techniques in designing contextualized language learning materials and supporting English language education in Indonesia. Further research is recommended to explore the long-term effects and applicability of scaffolding-based coursebooks across different grade levels and regions.